2021
DOI: 10.3390/ijerph18147241
|View full text |Cite
|
Sign up to set email alerts
|

Attachment, Emotion Dysregulation, and Physical IPV in Predominantly Hispanic, Young Adult Couples

Abstract: Insecure attachment has been found to be a risk factor for perpetrating physical intimate partner violence (IPV). However, this association is likely exacerbated by additional factors, such as conflicting insecure attachment in one’s partner and difficulties with overall emotion regulation and impulse control. The present study aimed to examine the associations between insecure attachment and physical IPV perpetration in male and female partners, as well as to examine whether these associations are exacerbated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…These findings are consistent with previous reports with non-clinical samples that indicate most IPV occurrences are bidirectional [ 17 , 67 ] and that women who report unilateral victimization represent a lower percentage of women involved in violent relationships [ 21 ]. Findings are also consistent with studies showing that emotional regulation [ 43 , 51 , 52 , 53 , 54 ] and attachment difficulties are implicated in both perpetration and victimization of violence [ 38 , 39 , 40 , 68 ]. More specifically, the findings from this study support an association between avoidant attachment and perpetration and anxious attachment and victimization in young adult Hispanic females.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These findings are consistent with previous reports with non-clinical samples that indicate most IPV occurrences are bidirectional [ 17 , 67 ] and that women who report unilateral victimization represent a lower percentage of women involved in violent relationships [ 21 ]. Findings are also consistent with studies showing that emotional regulation [ 43 , 51 , 52 , 53 , 54 ] and attachment difficulties are implicated in both perpetration and victimization of violence [ 38 , 39 , 40 , 68 ]. More specifically, the findings from this study support an association between avoidant attachment and perpetration and anxious attachment and victimization in young adult Hispanic females.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, Miga et al [ 42 ] did not find this attachment style related to such violence. However, other factors, such as interactions of different attachment styles may be at play, as illustrated by research that showed that attachment anxiety, impulsivity, and an interaction effect between attachment avoidance and partner′s attachment anxiety were associated with self-reported, but not partner-reported, male perpetration [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A mutual influence between couple relationship dynamics and individual emotion regulation has been documented by several scholars [ 81 , 82 , 83 ]. Violent behaviors may be seen as a way of avoiding taking contact with uncomfortable emotions regarding one’s intimate relationship and as a distance-regulating mechanism [ 84 , 85 ]. In this sense, isolating behaviors can be seen as a dysfunctional strategy used to control the degree of closeness within the couple′s relationship and thus regulate negative affect that can result from an imbalance between closeness and separation, to which people with low levels of emotional dysregulation can be more vulnerable.…”
Section: Discussionmentioning
confidence: 99%
“…The present study aims to study whether attachment styles could be a risk factor for alexithymia in male perpetrators of IPV confined in the Center for Behavioral Intervention for Male Aggressors in the Dominican Republic. As violence is also usually mediated by several factors, especially the quality of the parental relationship [ 10 , 27 , 28 , 29 ], the influence of this relationship has been also studied. Likewise, it intends to establish the socio-demographic profile of abusers with alexithymia in comparison with the non-alexithymia abuser‘s group.…”
Section: Introductionmentioning
confidence: 99%